Ticket to trade: Belgian labour and globalization before 19141 - Huberman, Michael (The Economic History Review, 2008)
Standard trade theory, as invoked by political scientists and economists, would anticipate that workers in Belgium, a small Old World country, rich in labour relative to land, were in a good position to benefit from the wave of globalization before 1914. However, wage increases remained modest and ‘labour’ moved slowly towards adopting a free-trade position. Beginning in 1885, the Belgian labour party backed free trade, but its support was conditional on more and better social legislation. Belgian workers' wellbeing improved in the wave of globalization, but the vehicle was labour and social legislation and not rising wages.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1468-0289.2007.00396.x